PELATIHAN PEMBUATAN PAKAN IKAN DARI BAHAN LOKAL: Training On Making Fish Feed from Local Ingredients - Irma El-Mira Husbuyanti; Denda Devi Sarah Mandini; Ismi Arifiana Rahmandari; Sandi Justitia Putra; Ni Kadek Puji Astuti; Luh Gede Sumahiradewi; Chairun Nufus; Cut Fanisha Dwi Efendi; Nova Susi Ayu Rahmawati (Al-Amal: Jurnal Pengabdian Masyarakat, 2026)
Rising commercial feed costs pose a major challenge for local fish farmers, as they inflate production expenses and reduce profit margins. This community service initiative aimed to enhance the knowledge and skills of fish farmers in producing high-quality, self-made feed using affordable and readily available local ingredients. The methods employed included educational sessions on fish nutrition, hands-on feed formulation workshops, practical feed production using grinding and pellet-molding machines, and questionnaire-based evaluations. The activity took place in Penimbung Village, involving the village government, local residents, university faculty and students, and fish farmers. Conducted by faculty members and students participating in the Student Community Service (KKN) program, the training—which encompassed team formation, planning, and the actual workshop—proceeded smoothly. The training featured hands-on practice, allowing participants to actively prepare and mix fish feed using local ingredients. This practical approach enabled participants to grasp technical aspects that theory alone cannot convey—such as texture, consistency, and aroma—while also allowing them to identify and correct errors in real-time. The hands-on nature of the training fostered enthusiasm and engagement, as participants could satisfy their curiosity and experience the process firsthand; ultimately, the initiative to produce fish feed using local ingredients was successfully executed.